Factors Affecting The Income Of Corn Farmers In Waihatu Village, West Kairatu District, West Part Of Seram District - silfana arifin; Leunard O. Kakisina; W. B. Parrera (Cita konsultindo, 2024)
This study aims to determine: (1) Corn farming income in Waihatu Village, West Kairatu District, West Seram Bagian Regency (2) Factors that affect the income of corn farmers in Waihatu Village, West Kairatu District, West Seram Bagian Regency. The research method used quantitative method. The sample location was determined deliberately, namely Waihatu Village in West Kairatu District. Sampling was taken 20% of the population of 210 corn farmers, then the sample used was 41 corn farmers. The first research objective, analyzed by the income formula and the second objective of the study using multiple linear regression analysis. The results showed that there are four factors that affect the income of corn farmers in Waihatu Village, West Kairatu District, West Seram based on four factors namely land area, production, production costs and selling prices. Based on the results of the simultaneous test / (F test) that all these factors together affect the income. And based on the partial test (t test) on three factors that have a positive and significant effect on income, namely production, production costs, selling prices and one factor that has a negative and significant effect on income, namely land area. Because in one planting area corn farmers only use most of the seeds and the other half of the land is used for other crops.